Arresting an Unusual Amide Tautomer Using Divalent Cations - Kashid, Somnath; Singh, Reman; Kwon, Hyejin; Kim, Yung Sam; Mukherjee, Arnab; Bagchi, Sayan (The Journal of Physical Chemistry B, 2019)
Ion-specific effects on peptides and proteins are key to biomolecular structure and stability. The subtle roles of the cations are far less understood, compared to the pronounced effects of the anions on proteins. Most importantly, divalent cations such as Ca2+ and Mg2+ are crucial to several biological functions. Herein, we demonstrate that an amide–iminolate equilibrium is triggered by the binding of the divalent cations to the amide oxygen in aqueous solution. The excellent agreement between the experimental and theoretical results confirms the arrest of an unusual amide tautomer by the divalent cations, which is a rarely known phenomenon that might open up an array of applications in chemistry and biology.
Keywords: Amides; spectroscopy